Formative Process Evaluation of the "Connect" Physical Activity Feasibility Trial for Adolescents. (June 2020) - Zarrett, Nicole; Abraczinskas, Michelle; Cook, Brittany S; Wilson, Dawn; Roberts, Alex
Most interventions do not reach full implementation in real-world settings. Due to this issue, formative process evaluation during pilot programs can be especially useful to understand implementation strengths and areas for improvement so that full implementation can be reached in future iterations. This study demonstrated how a formative process evaluation of the Connect through Positive Leisure Activities for Youth (Connect) pilot informed course corrections for year 2 implementation. Connect is an intervention to promote a positive social motivational climate for physical activity (PA) in pre-existing after school programs. Connect ran 3 days a week for 8 weeks and had 2 components: a 30-minute "Get-to-Know-You" (GTKY) session and a 60-minute PA session. Formative evaluation was assessed using an observational tool and staff surveys. Changes in youth PA during program hours was assessed as a process outcome using the System for Observing Children's Activity and Relationships during Play (SOCARP). All Connect essential elements were assessed with the observational tool including (a) social goal-oriented support; (b) collaborative, cooperative play; (c) equal treatment/access; and (d) an inclusive and engaging climate. Adequate dose was achieved on all items in all sessions. Although GTKY and PA sessions both reached high fidelity in promoting equal treatment and access, success in reaching fidelity varied for the 3 remaining essential elements. Post-intervention staff surveys indicated acceptability/adoptability of the Connect program and SOCARP observations indicated significant increases in PA from baseline to post-intervention. Changes for year 2 implementation based on the findings are discussed.